International Trade and Productivity Growth : Exploring the Sectoral Effects for Developing Countries - Choudhri, Ehsan; Hakura, Dalia (Washington, D.C. : International Monetary Fund, 2000)
The paper estimates an empirical relation based on Krugman's 'technological gap' model to explore the influence of the pattern of international trade and production on the overall productivity growth of a developing country. A key result is that increased import competition in medium-growth (but not in low- or high-growth) manufacturing sectors enhances overall productivity growth. The authors also find that a production-share weighted average of (technological leaders') sectoral productivity growth rates has a significant effect on the rate of aggregate productivity growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet